The Impact of a Web-Based Educational Initiative in Malang Regency: Enhancing Late Onset Hypogonadism (LOH) Awareness Through Community Service - Irnandi, Dicky Faizal; Hanggara, Dian Sukma; Khotimah, Husnul; Rifqi, Mochamad Shalahudin; Evangelista, Bernike Azza; Gonius, Andry; Kusdijanto, Amanda Yuanita (Universitas Airlangga, 2023)
Late Onset Hypogonadism (LOH), commonly known as andropause, poses significant hormonal challenges for elderly men, impacting their overall quality of life. With testosterone levels naturally declining from the age of 30 and accelerating beyond 40, this hormonal imbalance can manifest in symptoms that degrade the well-being of men. This community service initiative aimed to improve understanding and early detection of LOH among the Indonesian male population. A web-based application,